2006
DOI: 10.1167/iovs.05-1192
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Assessment of Presbyopia in the State of Andhra Pradesh, South India: The Andhra Pradesh Eye Disease Study

Abstract: The high prevalence of presbyopia and the stated effect on performing activities related to near vision needs to be translated into programs and strategies that specifically target presbyopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
130
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(161 citation statements)
references
References 26 publications
17
130
6
Order By: Relevance
“…8 The discovery that residing in a rural location is associated with the development of presbyopia has been replicated elsewhere. 9 In the same way, our study was undertaken exclusively in rurally located clusters, and our mean prevalence of presbyopia was higher in females. Female gender is consistently regarded as a risk factor for presbyopia, 7,10 which is an important revelation, because females are often less likely to receive ophthalmic treatment in low-income settings.…”
Section: U S O P H T H a L M I C R E V I E Wmentioning
confidence: 77%
“…8 The discovery that residing in a rural location is associated with the development of presbyopia has been replicated elsewhere. 9 In the same way, our study was undertaken exclusively in rurally located clusters, and our mean prevalence of presbyopia was higher in females. Female gender is consistently regarded as a risk factor for presbyopia, 7,10 which is an important revelation, because females are often less likely to receive ophthalmic treatment in low-income settings.…”
Section: U S O P H T H a L M I C R E V I E Wmentioning
confidence: 77%
“…Duarte et al, in Brazil estimated the prevalence of presbyopia in 3,000 adults of 30 years and older at 54.7 percent [22]. In southern India, Nirmalan et al, found a prevalence of 55 percent in subjects aged 30 years and older [23].…”
Section: Discussionmentioning
confidence: 99%
“…Testing both habitual distance visual acuity (uncorrected or with current correction) and corrected near visual acuity identifies refractive error or ocular disease and enables assessment of the patient's ability to function during near tasks. Patients underwent an ophthalmic examination that included Snellen Visual acuity, color vision, slit lamp biomicroscopy of the anterior segment as well as examination of the fundus [9]. Near vision was tested and corrected to the nearest +0.75 diopter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduction in the cost of glasses and treatment of complications due to government, insurance, or other external subsidies or by other means, such as the use of ready-made spectacles, 28 would likely improve acceptance and thus the effect on VA and costeffectiveness. However, other barriers besides cost, such as discomfort and lack of perceived need, 29 have been shown to reduce adult use of spectacles in LMICs. Approximately one-third (27.9% in Africa) to almost two-thirds (64.8% in Latin America) of patients could benefit from glasses for residual postoperative refractive error.…”
Section: Discussionmentioning
confidence: 99%